The production performance of native chicken by the utilization of Aleurites mollucana L. (pecan) seed flour in feeding - Jein Rinny Leke; E Wantasen; M Telleng; F N Sompie (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2019)
The study aimed to determine some effects of Aleurites Mollucana L (pecan) seed flour on the performance of native chicken production. Technically, this study used 100 native chickens. An experimental method was conducted using a completely randomized design (CRD). In addition, this research used 5 treatments with 5 replications. There were 25 experimental units, where each unit employed 4 native chickens. The treatments used were P0 (Control), P1 (Basal Feed + 1% of pecan seed flour), P2 (Basal Feed + 2% of pecan seed flour, P3 (Basal Feed + 3% of pecan seed flour), P4 (Basal Feed + 4% of pecan seed flour). Variables observed consist of weight of live native chicken, carcass’s weight and percentage, meat’s cholesterol and percentage, abdominal fatty’s percentage, spleen’s weight and percentage, heart’s weight, and percentage, and liver’s weight and percentage. Methodologically, data were analyzed using Analysis of Variance (ANOVA) from RAL. However, if there were differences between treatments and Duncan’s multiple distances, a further test was applied. As result, the study demonstrated that weight of live native chicken, carcass’s weight, abdominal fat percentage, spleen’s percentage, heart’s percentage, liver’s weight, and percentage had significant difference (P <0.01), but meat cholesterol, spleen’s weight, heart’s weight had insignificant difference (P> 0.05). It was concluded that the 4% addition of TBK (Aleurites Mollucana L), or pecan, seed flour, in feeding provided the best performance of native chicken’s production. Further, it was recommended to conduct a further study using pecan seed oil to reduce saponins in pecan seed.